2020
DOI: 10.4102/phcfm.v12i1.2563
|View full text |Cite
|
Sign up to set email alerts
|

Contracting of private medical practitioners in a National Health Insurance pilot district: What has been the effect on primary healthcare utilisation indicators?

Abstract: Background: In 2012, the National Department of Health in South Africa started contracting of private medical practitioners (MPs) as part of the first phase of National Health Insurance (NHI) in 11 pilot districts to improve access to healthcare.Aim: The aim of this study was to describe the effect of contracting private MPs on the utilisation of primary healthcare (PHC) services in public healthcare facilities.Setting: A National Health Insurance pilot district compared to a non-pilot district.Methods: A quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Te frequency of patient visits was associated with the family physicianpatient relationship, but not in an independent way [26]. However, in terms of family physician contract services, it was revealed that the increased utilization of PHC services in the pilot areas of the private practitioner contract system in South Africa might be the result of other health reforms rather than contracting with a family physician [27]. As for China, most relevant domestic studies have focused on residents' awareness of family physician contract services, willingness to contract, factors infuencing the contract decision, and the implementation of family physician contract service systems [28][29][30].…”
Section: Introductionmentioning
confidence: 95%
“…Te frequency of patient visits was associated with the family physicianpatient relationship, but not in an independent way [26]. However, in terms of family physician contract services, it was revealed that the increased utilization of PHC services in the pilot areas of the private practitioner contract system in South Africa might be the result of other health reforms rather than contracting with a family physician [27]. As for China, most relevant domestic studies have focused on residents' awareness of family physician contract services, willingness to contract, factors infuencing the contract decision, and the implementation of family physician contract service systems [28][29][30].…”
Section: Introductionmentioning
confidence: 95%
“…Others have hypothesised that perceived improved quality of care at PHC facilities would lead to high volumes of clients and that MPs would have an increased workload, to which they would respond by increasing referrals to the next level of care (Groenewegen & Hutten 1991:1111-1119. However, studies have shown that the increase in the utilisation of PHC services in NHI pilot districts cannot be attributed only to the contracting of private MPs (Mukudu et al 2020). This raises questions about the appropriate measure of the quality of care in view of simultaneous implementation of other aspects of PHC re-engineering and healthcare reforms such as ward-based outreach teams (WBOTs), district clinical specialist teams (DCSTs), centralised chronic medicine dispensing and distribution (CCMDD), Ideal Clinic Realisation and Integrated School Health Programme (ISHP) (Naledi, Barron & Schneider 2011:17-28).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Similarly, adherence to referral guidelines has been poor from both PHC and OPDs. [19,20] In the immediate post-NHI pilot implementation in Tshwane district, some studies have shown a decrease in utilisation of PHC services and improvement in perception of quality of PHC services, as evidenced by reduction in self-referral headcounts in OPD, [21,22] but the long-term impact is not known. Despite successes noted in the NHI pilot evaluation report, [23] several gaps in provision of PHC still exist, such as lack of medical equipment, inadequate monitoring of contracted MPs, lack of critical medical specialists, lack of integration of different aspects of the project and inability to adequately monitor effectiveness of the referral system.…”
mentioning
confidence: 99%